Performance of Newly Released Dry Land Wheat Varieties under Barani and Minor Irrigated Conditions (Biological Sciences - PJSIR, 2008)
. Among the three newly released dry land wheat varieties viz; Marwat J-01, Lucky J-03 and Raj 2000 and the local race “Khattakwal wheat” sowed in district Karak during, November, 2004-05, significant difference was found between the grain yields both under barani and minor irrigated environment. Marwat J-01 out yielded significantly all the varieties with one irrigation (4120 kg/ha) followed by Raj-2000 (3993 kg/ha). Under barani conditions as well, the two varieties produced statistically equal but highest grain yield of 1718 and 1773 kg/ha, respectively